Complete closure of a colo-duodenal fistula in a patient with advanced ascending colon cancer after pembrolizumab combined with radiation therapy: a case report - Tetsuro Tominaga; Takashi Nonaka; Akiko Fukuda; Masaaki Moriyama; Shosaburo Oyama; Mitsutoshi Ishii; Masato Nishimuta; Yuta Fujise; Terumitsu Sawai; Takeshi Nagayasu (Surgical Case Reports, 2021)
Abstract Background A colo-duodenal fistula is a very rare complication of colon cancer that presents with not only severe clinical symptoms, but a poor prognosis due to locally advanced cancer. A novel immune checkpoint inhibitor for colon cancer patients provides a high objective response rate. Recently, radiation therapy combined with immune checkpoint inhibitor therapy has been reported to have a synergistic antitumor effect. A case of complete closure of a colo-duodenal fistula in a patient with locally advanced colon cancer after combined pembrolizumab and radiation therapy is reported. Case presentation A 66-year-old man presented with abdominal distention. Abdominal contrast-enhanced computed tomography (CT) showed a 80-mm bulky mass in the right upper quadrant. The tumor created a fistula to the second portion of the duodenum. Upper gastrointestinal endoscopy showed a colo-duodenal fistula. Gastro-jejunal bypass and ileostomy were performed to prevent bowel obstruction, followed by systemic chemotherapy. MSI-high was diagnosed on examination of the biopsy specimen. Treatment was then changed to immunotherapy using pembrolizumab; after six courses, the tumor markers were decreased to within normal ranges, but the main tumor increased. Radiation therapy was then given for local control of the main tumor, after which CT showed that all of the tumor, including the main tumor, lymph node metastases, and the colo-duodenal fistula, had gradually shrunk. Follow-up upper gastrointestinal endoscopy showed that the colo-duodenal fistula had closed completely. PET–CT showed no abnormal uptake in all tumors, and clinical complete response was diagnosed. Now, 21 months after diagnosis, the tumor is well controlled without evidence of regrowth. Conclusions Pembrolizumab combined with radiation therapy has a potentially dramatic therapeutic effect for advanced colon cancer.